Six Sigma and FMEA Methods for Cause Analysis of the Defects in PT.X - Utami, Ria Oktavia Putri; Harwati (Universitas Mulawarman, 2024)
The manufacturing sector is currently competing against each other to always get market share. In achieving the vision and mission, the company must use one’s strength to increase production and product quality. PT. X is a manufacturing company that manufactures piano musical instruments that continually do improve to increase quality to meet customer needs. This research used the Six Sigma and FMEA methods to minimize defects that occur. The results of calculations obtained Upright Piano (UP) PM / PW which has the highest reject value. The average value of DPMO for 8 months was 16294.57, and the sigma value was 3.62. The results of identifying the type of defect that is often the cause of reject cabinet using a Pareto diagram is the muke permukaan with a percentage of 24.03%. The dominant cause of the defect occurs because during the sanding process the position of the Ategi is tilted when at the edge and the operator's ability is not evenly distributed. Improvement that can be given during the sanding process Ategi’s position tilted when at the edge of the position Ategi must be flat when at the edge of the cabinet and the balance when making the sanding process must be maintained properly. Improvement for the ability of operators that have not been evenly distributed, namely conducting training on basic skills to all operators who have worked for a long time, implementing the OJT (On the Job Training) program during probation, and sharing knowledge.